Documenting the traditional burial customs in Banaue, Ifugao - Bahatan, Alexis Pia Khrystel S. (School of Library and Information Studies, University of the Philippines, Diliman, 2019)
Our culture paves the way to forge our identity. The town of Banaue, Ifugao holds a deep-rooted and rich culture, which has been passed to them from generations through oral narratives and by practice. They have a certain ritual for every occasion, birthday, house blessing, anniversaries, engagements, and even death. But with the emergence of technology, religion, and the surge of tourists that stay longer than necessary in Banaue, their culture is slowly being watered down to conform to these rapid changes. Having their culture, traditions, and rituals passed on by their elders through oral narratives, and with these new generation of elders slowly losing their sanity to old age or an illness, they needed a written transcript of how things are done in their village. Thus, the birth of this study, to help immortalize the burial customs in Banaue, Ifugao through documentation.